Быть любимой: [роман] / Людмила Белякова - Белякова Людмила Игоревна (Женские истории, 2004)
Экземпляры: ЧЗ (20181107) / Инвентарный номер: 44471 / Цена: 20 / Авт.знак: Б 44 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6